2014
DOI: 10.1109/tcomm.2014.021614.130172
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a Tradeoff between Completion Time and Decoding Delay in Instantly Decodable Network Coded Systems

Abstract: This paper studies the complicated interplay of the completion time (as a measure of throughput) and the decoding delay performance in instantly decodable network coded (IDNC) systems over wireless broadcast erasure channels with memory, and proposes two new algorithms that improve the balance between the completion time and decoding delay of broadcasting a block of packets. We first formulate the IDNC packet selection problem that provides joint control of the completion time and decoding delay as a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…By doing so, IDNC guarantees a subset of (or if possible, all) receivers be able to instantly decode one of their wanted packets upon successful reception of the coded packet. [27][28][29] Moreover, IDNC encoding can be implemented using binary XOR, which eliminates complicated operations over large Galois fields as required by RLNC.…”
Section: Network Coding For Data Dissemination In Vanetsmentioning
confidence: 99%
“…By doing so, IDNC guarantees a subset of (or if possible, all) receivers be able to instantly decode one of their wanted packets upon successful reception of the coded packet. [27][28][29] Moreover, IDNC encoding can be implemented using binary XOR, which eliminates complicated operations over large Galois fields as required by RLNC.…”
Section: Network Coding For Data Dissemination In Vanetsmentioning
confidence: 99%
“…However, the works in [34,38] showed that finding the optimal IDNC schedule for wireless broadcast of a set of packets is computationally intractable due to the curse of dimensionality of the dynamic programming approach. Therefore, to efficiently solve the optimization problem in (4) with much lower computational complexity, we draw several guidelines for the prioritized IDNC algorithms in the following three subsections.…”
Section: Maximizing the Minimum Decoded Video Layers Problem Formulationmentioning
confidence: 99%
“…This heuristic algorithm selects maximal cliques κ c and κ b based on a greedy vertex search over IDNC graphs G 1: c and G 1: b (κ c ), respectively. A similar greedy vertex search approach was studied in [34,38] due to its computational simplicity. However, the works in [34,38] solved different problems and ignored the dependency between source packets and the hard deadline.…”
Section: Heuristic Packet Selection Algorithm Over a Given Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…Although G-IDNC has been extensively studied under various wireless broadcast settings, including basic ones [12,12,[22][23][24][25][26][27][28] and those with limited/lossy feedback [29,30] or with hard deadline [31], most developed algorithms are heuristics, leaving the optimal G-IDNC in terms of throughput and APDD still unknown or intractable due to prohibitively large computational complexity. Hence in this paper, we take a step back, aiming to understand the performance limits and optimal implementations of a sub-class of G-IDNC, namely, S-IDNC.…”
Section: Introductionmentioning
confidence: 99%